(untitled) (Research, Society and Development, 2020)
Faced with the role of antioxidants in preventing the genesis of various diseases, the interest of the population and the food industry, research in this field has been intensified. In this context, the fruits of the carnauba palm, rich in vitamin C and anthocyanins, stand out, but have a high perishability, which increases their waste in harvest periods. This makes it essential to process them into jelly. Another fruit rich in anthocyanins is the Isabel grape. Thus, the objective was to evaluate the antioxidant capacity of a mixed carnauba and grape jelly, as well as to compare it with fruit jellies made separately. For this, 3 jelly formulations (grape; carnauba; mixed) were produced and the antioxidant activities, FRAP and ABTS, of the extracts produced from these were analyzed. It was observed that the junction of carnauba with grape intensified the ABTS antioxidant activity, while for FRAP there was no difference compared to grape jelly. In view of this, it was found that the use of carnauba with the grape in the manufacture of a jelly is extremely important to achieve greater antioxidant activity and obtain a functional product active in preventing the genesis of several chronic non-communicable diseases.